Implementing atomic objects with the RelaX transaction facility. - CAHILL, VINNY (My University, 1992)
RelaX offers an extensible transaction facility which isolates distributed (thus complex) transaction processing. A distributed system providing basic support for local recovery may easily be enhanced with flexible transaction functionality by linking it to the RelaX facility. The work described is being carried out in conjunction with the European ESPRIT Comandos project. In the Comandos platform, the transaction facility is used to implement atomic objects
PUBLISHED
Palo Alto, CA, USA Also available om Computing Systems 5(3) 1992 pp259-304
Keywords: Computer Science